KEPEMIMPINAN PELAYAN MEMODERASI PENGARUH PEMBERDAYAAN TERHADAP PERILAKU IMPLEMENTASI INOVASI - Sasmita Putri, Luh Gede Dhavantari; Utama, I Wayan Mudiartha (E-Jurnal Manajemen, 2018)
The purpose of this research is to examine the role of servant leaderhsip to moderate the influence of empowerment on innovation implementation behavior on the employees of Taman Amertha Villa Seminyak Bali by using the census method (total sampling) in determining the sample of 53 respondents, then analyzed by moderation regression technique (MRA). The analysis results show that empowerment has a positive influence on innovation implementation behavior. Servant leadership has a positive influence on innovation implementation behavior. Servant leadership moderation the influence of empowerment on innovation implementation behavior. Suggestions to the leadership of the company must apply empowerment with training, education in helping each employee to hone skills so as to have the readiness and skill in completing the work. Servant leadership attitudes are maintained to create a safe and comfortable atmosphere by understanding the work situation to consider employee suggestions and inputs so that they act correctly when making decisions.